A novel role of the ferric reductase Cfl1 in cell wall integrity, mitochondrial function, and invasion to host cells in Candida albicans. Issue 7 (28th August 2014) - Yu, Qilin; Dong, Yijie; Xu, Ning; Qian, Kefan; Chen, Yulu; Zhang, Biao; Xing, Laijun; Li, Mingchun
Abstract Candida albicans is an important opportunistic pathogen, causing both superficial mucosal infections and life‐threatening systemic diseases. Iron acquisition is an important factor for pathogen–host interaction and also a significant element for the pathogenicity of this organism. Ferric reductases, which convert ferric iron into ferrous iron, are important components of the high‐affinity iron uptake system. Sequence analyses have identified at least 17 putative ferric reductase genes in C. albicans genome. CFL1 was the first ferric reductase identified in C. albicans. However, little is known about its roles in C. albicans physiology and pathogenicity. In this study, we found that disruption of CFL1 led to hypersensitivity to chemical and physical cell wall stresses, activation of the cell wall integrity (CWI) pathway, abnormal cell wall composition, and enhanced secretion, indicating a defect in CWI in this mutant. Moreover, this mutant showed abnormal mitochondrial activity and morphology, suggesting a link between ferric reductases and mitochondrial function. In addition, this mutant displayed decreased ability of adhesion to both the polystyrene microplates and buccal epithelial cells and invasion of host epithelial cells. These findings revealed a novel role of C. albicans Cfl1 in maintenance of CWI, mitochondrial function, and interaction between this pathogen and the host.